Craving of addictive substances and the dreams related with these substances - Gürpınar, Dilek; Tokuçoğlu, Levent (Journal of Dependence, 2006)
It is an important step to understand the neuroanatomical origin of the addictive substance craving and to find its neuroanatomical relationships in comprehending substance addiction and its treatment. Drives, wishes and dreams are originated from me-solymbic reward system which extends from ventral tegmental area to nucleus accumbens and has projections to limbic system and orbitofrontal cortex. Addictive substances increase substance craving and cause addiction by giving rise to upregulation of pathways in this area. There is a high risk of substance addiction in people exposed to cigarette or other addictive substances during the years of childhood. Addicted people have frequent dreams relating to addictive substances. Dreams are also originated from ventral tegmental area just like drives, wishes and substance craving. Because of this reason, the dreams show the way to the psychotherapist about the strength of substance craving and wish.